Understanding e-Loyalty in Online Grocery Shopping - Kaukab Abid Azhar; Dr. Muhammad Adnan Bashir (International Journal of Applied Business and International Management, 2018)
Online grocery stores are becoming more popular than ever. As the number of consumers of online grocery stores increases, understanding e-loyalty in this context is pivotal. Despite its growing importance, e-loyalty in online grocery shopping is a less explored area in expanding e-commerce literature. The purpose of this research is to examine and understand the mediating role of e-satisfaction on e-loyalty in context of online grocery shopping. Predictors (convenience, merchandising, site design, and financial security) identified in Szymanski and Hise’s e-satisfaction model are used to further extend the model by examining their relationship with e-loyalty through mediation from e-satisfaction. The proposed model was tested on a sample of 351 online shoppers through the database of two large online grocery stores in Pakistan. The results were measured through regression analysis. Findings suggest that there is no significant relationship between any of the variables under study. Moreover, the mediating effect of e-satisfaction on e-loyalty was also not found. The results indicate significant contribution in three main areas: provides new insights for understanding e-loyalty, rejects Szymanski and Hise’s e-satisfaction model in the context of online grocery shopping, and validates findings of previous researchers who had suggested distinguish nature of online grocery shopping. Managers need to adopt different strategies for online grocery shopping due to the perishable and variable nature of the products. Some other variables can also be added to the model, such as e-trust and e-service quality, to further validate the research model.